Laulības starp Imperiālās Ķīnas un tās kaimiņvalstu aristokrātu ģimenēm - Zolotarjova, Anastasija (Latvijas Universitāte, 2014)
Šī maģistra darba nosaukums ir „Laulības starp Imperiālās Ķīnas un tās kaimiņvalstu aristokrātu ģimenēm”. Tajā apskatīta hecjiņ jeb Ķīnas imperatora meitu vai māsu izdošana par sievām ārzemju tautu valdniekiem ar nolūku nepieļaut šo tautu karaspēku iebrukšanu Ķīnā.Darba mērķis ir hecjiņ līgumu slēgšanas tradīcijas izpēte, apskatot vairākus šāda veida laulību gadījumus. Darba gaitā tika noskaidrots, ka ķīniešu un nomadu tautu attieksme pret laulībām starp Ķīnas un kaimiņvalstu aristokrātu ģimenēm ir ļoti atšķirīga. Šādu laulību slēgšanas iemesls bieži vien bija Ķīnas politiskais vai militārais vājums. Darbs sastāv no 3 daļām: 1."Hecjiņ tradīcija"; 2."Iemesli laulībām starp Ķīnas un tās kaimiņu aristokrātu ģimenēm"; 3."Starpvalstu laulību gadījumi". Darba apjoms ir 65 lpp.

Title of this master’s thesis is „Marriages between noble families of Imperial China and its neighbouring countries”. It examines the tradition of „heqin” or the marriage of China emperors daughters or sisters to foreign nation’s leaders with a view to prevent this nation’s troops invasion of China. The aim of this work is to study heqin tradition by examining various cases of heqin marriage conduction. During the research it was found that chinese and nomad people’s attitude towards marriages between noble families of Imperial China and its neighbouring countries is very different. The reason for proposing such marriages was the political or military weakness of China. The thesis consists of 3 parts: „Heqin tradition”; „The reasons for marriages between noble families of Imperial China and its neighbouring countries”; „Cases of cross-border marriages”. Total size of this paper is 65 pages. Key words: political marriage; heqin tradition; nomadic people; foreign relations of China
Marriages between Noble Families of Imperial China and its Neighbouring Countries
Keywords: Valodniecība